Effectiveness of Android-Based Learning Media in Digital Simulation Subjects - Saputri, Renny Permata; Fransisca, Monica (The Indonesian Journal of Computer Science, 2023)
The increasingly rapid digital development demands that the learning media used can attract students' interest and attention. The research method used is Research and Development with 4D development stages (Define, Design, Develop, Disseminate). The aim of this research is to determine the effectiveness of Android-based learning media in digital simulation subjects at Padang City Vocational Schools. The research population was 73 Padang City Vocational High School students who were randomly selected from SMKN 1 Padang, SMKN 2 Padang, and SMKN 4 Padang. Based on data from the effectiveness test results, the average effectiveness was 84.96%. So it can be concluded that the use of Android-based learning media in digital simulation subjects at the Padang City Vocational High School is categorized as an effective media.